(untitled) (International Journal of Engineering and Computer Science, 2015)
Due to continued increase in crime rate, the security of life, property and infrastructure has been an issue of national concern over the years and increasingly so all over the world. This paper presents a method of identifying clients that request for real-time surveillance security service activated by SMS or phone call in event of invasion or suspected robbery attack. Recognition of DTMF (Dual Tone Multi Frequency) tones produced by the buttons pushed on client’s telephone keypads was done using Goertzel algorithm which is a digital processing technique that provides a means for efficient evaluation of individual terms of the Discrete Fourier Transform (DFT).The proposed GPS-based Real-time Security System (GRSS) is proposed to offer on-demand video capture using indoor cameras and outdoor surveillance cameras, transmit the data wirelessly to a remote data centre for monitoring via IP (Internet Protocol) technology. The Master control station should be able to receive a Save Our Soul (SOS) alert from a subscriber either by GSM (Global System for Mobile communications) call or SMS (Short Message Service), determine the sub control station in charge of the client’s zone and transfer control to it. The station in charge should now pinpoint the client’s location using Global Positioning System (GPS) based location data stored in the database, and trigger relevant components for surveillance action over the area. The system features a flexible and scalable remote automated client identification system for the proposed on-demand GPS based real-time security service system.